Towards Sustainable Development in Central America and the Caribbean - Danielson, Anders; Dijkstra, A. Geske (Palgrave Macmillan UK, 2001)
Since the economic decline in the early 1980s, most countries in Central America and the Caribbean have returned to positive growth rates. The recovery often coincided with or followed extensive neoliberal reforms. The contributors to this book address the crucial question of whether these growth rates are sustainable. Several aspects of sustainability are assessed, in particular macroeconomic, social, and ecological aspects. The book includes both comparative analyses focusing on one of these aspects of sustainability, and country case studies. The conclusion is that these countries have not yet arrived at a sustainable growth path due to, for example, high levels of foreign and domestic debt, worrisome trade gaps, a lack of social integration and irresponsible exploitation of natural resources. In sum, the analysis points to serious weaknesses in the current neoliberal model, the implications of which go far beyond this particular region
Keywords: Industrial management / Environmental aspects; America / History; Sustainable development; Development economics